Approaches for Mastering Coordinative Appositions Exceptions in Simple Present Tense - Farisani Thomas Nephawe; Matodzi Nancy Lambani (JETL (Journal of Education, Teaching and Learning), 2022)
Coordinative appositions bring coordination between words, phrases, and clauses in communication. They are one grammatical feature requiring second language learners’ competence in its usage. However, the use of the coordinative appositions exceptions in English language is concerning. They usually deviate from the exceptions involved in the use of the coordinating conjunction ‘and’ in the simple present tense. In South African schools, English First Additional Language learners are affected by this learning adversity. The research paper aimed at investigating a suitable approach for mastering the coordinative appositions exceptions in the simple present tense. A quantitative research approach was used by the researchers because the findings could be reduced to numbers and percentages using statistical procedures. Using a questionnaire, data were collected from the respondents. Statistical Package for Social Sciences version 22 and IBM SPSS version 25 both were utilised to analyse data after the findings from each software were collated for validity purposes. A random sampling technique was used to sample 8 respondents from an overall enrolment of 65 Grade eight learners at Andries Mugaguli Secondary School in Limpopo Province, South Africa. Although pre-test findings showed poor performance in using ‘Hangman’ approach, after utilising the ‘coordinating conjunction board game, learners’ performance improved remarkably. The research recommends regular practise in the exceptions involved in the use of the coordinating conjunction ‘and’ in the simple present tense.